2022
DOI: 10.1155/2022/7312960
|View full text |Cite|
|
Sign up to set email alerts
|

Effect of Percutaneous Nephrolithotomy Combined with Needle Nephrolithotomy on Renal Function and Complication Rate in Patients with Complex Renal Calculi

Abstract: Objective. To investigate the effect of percutaneous nephrolithotomy combined with needle nephrolithotomy on renal function and incidence of complications in patients with complex renal calculi. Methods. From March 2020 to March 2022, 88 patients with complex renal calculi were enrolled and divided into two groups. Percutaneous nephrolithotomy (PCNL) was performed in the control group, and percutaneous nephrolithotomy combined with needle nephrolithotomy was performed in the study group. Perioperative conditio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 18 publications
(18 reference statements)
0
2
0
Order By: Relevance
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%